How the ThinkPad changed the world: And is shaping the future - Arimasa Naitoh (Skyhorse, 2017)
In this book, Arimasa Naitoh, the father of the ThinkPad, collaborates with American business journalist and author William J. Holstein to write candidly about the incredible technological and personal struggles he and fellow engineers faced. And he offers his vision of the future of mobile computing--because this revolution is not even close to being finished.